Supply Chain Risk Management: Sustainable Waste Management Strategy, Empirical Study at KUPAS Panggungharjo Village - Ziyadatul Rachmah; Aris Kusumo Diantoro (UPN Veteran Yogyakarta, 2022)
KUPAS Panggungharjo Village is a business unit that manages waste so that it can be reused. Based on the results of field studies, there are several risks that hinder the flow of Supply Chain in KUPAS and also previously in KUPAS itself, risko studies have never been carried out. Therefore, it is necessary to map Supply Chain performance activities and identify risks that exist in supply chain flows in KUPAS. This study aims to identify what risks exist in the Supply Chain flow in KUPAS by using the Supply Chain Operation Refence (SCOR) method to determine the mapping of Supply Chain flows then using the House of Risk method to identify the risks that exist in the Supply Chain flow the one in KUPAS. Data collection techniques use interviews and observations. Interviews were conducted with informants who had been selected from purposive sampling techniques, namely to kupas employees and customers. Based on the results of the study, it is known that the Supply Chain performance is good, it can be seen from the total value of supply chain performance in KUPAS, which is 67.27. Meanwhile, the results of risk identification using the HOR method there are 4 sources of risk in KUPAS.